Media warfare: a global challenge in the 21st century / Assoc. Prof. Mohd Rajib Ghani - Ghani, Mohd Rajib (CMIWS and UiTM Press, 2008)
We all know that the rise of Islamic fundamentalists and radicals has provided the world with tremendous challenges in the field of international terrorism. Yet, especially after the downfall of the Shah in 1979, the long-established international state system has also faced a challenge in the form of the Iranian Islamic Republic, which created a governing system that challenged the western concept of government.